2016
DOI: 10.1021/acs.joc.5b02554
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Tetrasubstituted Propargylamines via Hydroamination and Metalation of 1-Alkynes and Their Enantioselective Conversion to Trisubstituted Chiral Allenes

Abstract: Reaction of cyclic secondary amines with 1-alkynes and copper(I) chloride at 110-120 °C gives the corresponding alkynylcopper complex, which adds to the iminium ion intermediate formed in situ by hydroamination of 1-alkynes to give the corresponding propargylamine derivatives in up to 94% yield and 99% regioselectivity. The diastereomerically pure chiral propargylamines were obtained in 23-89% yield using optically active 2-benzyl morpholine and N-methyl camphanyl piperazine. These chiral propargylamines are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(8 reference statements)
0
24
0
Order By: Relevance
“…More specifically, enamines, deriving from hydroamination of the alkyne, were frequently observed during our studies (detected by GC/MS analysis and also identified by their characteristic peaks in the 1 H NMR spectra of column chromatography fractions). 20 It is important to note that propargylamines originating from the alkynylation of ketiminium intermediates deriving from these enamines were never observed. 20d Repeating the reaction in toluene (1 M) at 120 °C, simultaneously increased product yield and significantly reduced the amounts of side products (entry 2, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, enamines, deriving from hydroamination of the alkyne, were frequently observed during our studies (detected by GC/MS analysis and also identified by their characteristic peaks in the 1 H NMR spectra of column chromatography fractions). 20 It is important to note that propargylamines originating from the alkynylation of ketiminium intermediates deriving from these enamines were never observed. 20d Repeating the reaction in toluene (1 M) at 120 °C, simultaneously increased product yield and significantly reduced the amounts of side products (entry 2, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Gaining access to ketone-derived, tetrasubstituted (or α-tertiary) propargylamines through a catalytic, multicomponent coupling is a worthy goal, considering the wide array of natural products that possess α-tertiary amine moieties, 19 the intrinsic value of propargylamines and the inherently limited scope of other strategies used to access such molecules. 20 The difficulty of this task was demonstrated by Ramón and co-workers in 2010, when a maximum of 38% yield was achieved after 7 days of reaction between piperidine, 3-pentanone and phenylacetylene, catalyzed by the otherwise efficient Cu(OH) x –Fe 3 O 4 catalyst. 21 The first breakthrough was made by Van der Eycken and co-workers, who exploited the enhanced reactivity of cyclohexanones to construct propargylamines derived from cyclohexanones, benzylamines, and phenylacetylene under homogeneous, solvent-less CuI catalysis, and microwave irradiation, also coining the term “KA 2 coupling” (ketone, amine, alkyne—Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of ketone-derived, tetrasubstituted propargylamines, through a catalytic, multicomponent coupling strategy, was attempted by several research teams, considering the great abundance of different natural products that possess α-tertiary amine moieties, [53] along with the inherent value of propargylamines and the scarcity of synthetic strategies leading to such molecular scaffolds. [54][55][56][57] An early related example was demonstrated by Ramón and co-workers in 2010, when the desired product was obtained in 38% yield after 7 days of reaction between piperidine, 3-pentanone, and phenylacetylene, catalyzed by Cu (OH) x -Fe 3 O 4 as the catalyst. [58] Nonetheless, the first breakthrough was made when the research group of Van der Eycken successfully prepared various tetrasubstituted propargylamines, derived from cyclohexanones, benzylamines and phenylacetylene, using a homogeneous, CuI-based and microwave-assisted catalytic system, under neat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Propargylamines exhibit biological properties, such as anti-Alzheimer, anti-Parkinsonian, and antidepressant activities 35 . Methods used to prepare propargylamines include amination of propargylic electrophiles 6 , nucleophilic addition of alkynes to imines or enamines 7 , and three-component (aldehyde, terminal alkyne, and amine, A 3 ) coupling reactions through C–H activation 8,9 . Among these synthetic strategies, A 3 coupling is the most efficient, and it permits construction of complex structures from simple starting materials with water as byproduct 10,11 .…”
Section: Introductionmentioning
confidence: 99%